Green data centre : power management - Wong, Way-ne (2017)
Rising demand for IT services has increased the number of servers necessary to support this trend. This results in either more datacenters being built or existing locations being packed more densely. Most datacenters were designed only for reliability and did not incorporate energy efficiency into their design. With more and more services being delivered by the cloud served from a datacenter, the share of overall global energy going towards powering and cooling these facilities is increasing.